MONITORING KONDISI JANTUNG MENGGUNAKAN SMS GATEWAY - Muhammad Hasan; Muhammad Fiqhi Ibad; Yudha Trio; Dina Takti Makhfufah; Andriani Parastiwi (SENTIA 2016, 2016)
The heart is the most important organ in the human body, in this body, heart has the function of blood flow to the lungs and to the rest of the body. Humans can know the body's health by conducting health tests at the hospital. But in fact humans are too busy with their activity or constrained problems cost for checked his health. The death rate increasing every year due to the delay of someone knowing his illness. From this issue, then designed a tool that can monitor heart condition diagnosis about changes the pulse that detected by method of photoplethysmography. This tool designed with LCD display that can showing the beats per minute (BPM), in addition, include other smart sensors such as GPS and sensor photoplethysmography. The workings of the tool to be created to read the pulse and converted into BPM, then the results of the diagnosis can be monitored viaSMS Gateway. The tool created with the emergency notification if detect an abnormal condition of the pulse (heart), a notification sent by SMS Gateway that containing an abnormal condition and GPS data, GPS data is used to determine the position where the patient is ill, so the patient can be rescue immediately.